Patterns of land use, zoning and economies of scale in cities: three essays on urban economics for Brazil - LIMA, Ricardo Carvalho de Andrade (2018)
This thesis is divided into three empirical essays in the field of urban economics, analyzing the case of Brazilian cities. The first essay uses a novelty microdata of 98,198 individual parcels in the city of Recife to investigate the determinants of the urban land use. Through a semi-parametric spatial econometric approach, it is observed that there are considerable local spatial effects. In addition, we note some regularities in the spatial distribution of urban land use. Transport infrastructures tend to attract the development of commercial activities, while natural amenities encourage residential land use. The objective of the second essay is to evaluating the impact of zoning ordinances on the housing market. Using matching methods and a dataset covering all Brazilian municipalities, we evidenced that zoning generates an increment ranging from 5.4% to 6.3% on the average rents, but do not affect the house growth. In addition, we conducted sensitivity analyses that suggests that this result is not simply driven by unobservable confounders. Finally, the third essay investigates the impact of municipal secession on local public expenditures through a Differences-in-Differences approach. The results indicate that those municipalities that experienced a secession process increased their per capita capital expenditures by 14.7%. In addition, we show evidence that suggests that this increase in expenses can be explained by a reduction in economies of scale and rent-seeking behavior.